SWOT Analysis of Pakistan Education System: Impact of China- Pakistan Economic Corridor - khalid, Sabika; Tadesse, Endale; Muhua, Wang; Lei , Deng (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The aim of the study is to review the impact of China-Pakistan Economic Corridor on the Pakistani educational sector. Furthermore, the study critically examines the present educational challenges of the Pakistan education system and CPEC logistics arrangement between China and Pakistan. Approach/Methodology/Design: We analyzed literature through SWOT analysis to review the strengths, weaknesses, opportunities, and threats in the context of education. Findings: The analysis indicated that CPEC not only benefits the economy and bilateral trade between the two countries but it also offers opportunity for Pakistan to adopt and access more policies to strengthen the educational sector of the country. The SWOT analysis also demonstrates that CPEC has more venues of opportunity rather than threats. Practical Implications: The study offers an overview of CPEC effect on education in Pakistan. Though it is mainly economy-driven, this study analyzes the CPEC with a focus on the effects on the educational system in Pakistan. This opens a venue for more engagement between the two countries in terms of training, academic exchange, and educational planning. Originality/value: This study examines the effects of CPEC on the education system in Pakistan. Most of the literature on CPEC is concerned about the economic effect. This study investigates how CPEC impacts the educational aspects in Pakistan.